Review of the 2021 ChinaCALL conference - Zhang Shuai; Wang Qi (Journal of China Computer-Assisted Language Learning)
This paper aims to provide an overview of the 2021 ChinaCALL conference. The topics range from the traditional ones of teaching, learning and assessment to the emerging fields of intelligent computer-assisted language learning (iCALL), conversational agents and language development, the reconceptualisation of teacher digital literacy, reflections upon perfunctory gamification in language learning and particularly pedagogy in the post-pandemic era. In addition, the ability of technology to facilitate language education is explored, along with its potential to foster teacher and learner well-being.